Generalization of the theory of critical distance to estimate lifetime of notched components in the medium-cycle fatigue regime - Borges Rafael; Araújo José; Silva Cosme; Dias Jéssica; Ferreira Jorge (MATEC Web of Conferences, 2019)
This paper proposes a new and improved way to determine the dependency of the parameter that characterizes the process zone size ∫ with fatigue life Nf. Thus, unlike the classical approach, this approach has the advantage of allowing the construction of a ∫ versus Nf relationship, which is independent of the type of test used for calibration. In order to define the new relationship, a calibration strategy is presented considering the critical plane models based on the Fatemi-Socie and Smith-Watson-Topper. The accuracy of the method is verified by using data sets taken from the literature. A study on the effect of stress ratio (R) on the behaviour of the ∫ versus Nf relationship is presented and indicates that, although such relationship seems to depend on the R value used in the calibration, the life predictions obtained by these relationships are statistically similar.